1980
DOI: 10.1126/science.210.4476.1356
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Species in Fly Ash from Coal-Burning Power Plants

Abstract: Fly ash specimens from four power plants in the Tennessee Valley Authority system have been separated into three matrices: glass, mullite-quartz, and magnetic spinel. Chemical species of trace elements are defined to a large extent by the matrices that contain them. The magnetic component of fly ash is ferrite. The mullite-quartz phase is relatively pure and can be recovered as a resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(96 citation statements)
references
References 5 publications
5
89
0
2
Order By: Relevance
“…No diffusion or reaction within the clusters and the rest of the sample occurred probably because the coarse Ba-aluminates were in equilibrium at local level with Celsian, and thus, it was not possible to eliminate them by heat treatment. However, most of the BaAl 2 0 4 formed by the mechanism explained above was slowly consumed by reaction (15) in the temperature range of 900-1300 °C, involving the participation of free crystalline quartz and Si0 2 contained in the glassy phase, both of them present in the CFA. (15) At ^1300 °C the last BaSi 2 Os remaining could be also completely consumed by ALO3 contained in the remnant glassy phase of the CFA, according to reaction (8).…”
Section: Reaction Mechanism For the Formation Of Celsianmentioning
confidence: 99%
See 1 more Smart Citation
“…No diffusion or reaction within the clusters and the rest of the sample occurred probably because the coarse Ba-aluminates were in equilibrium at local level with Celsian, and thus, it was not possible to eliminate them by heat treatment. However, most of the BaAl 2 0 4 formed by the mechanism explained above was slowly consumed by reaction (15) in the temperature range of 900-1300 °C, involving the participation of free crystalline quartz and Si0 2 contained in the glassy phase, both of them present in the CFA. (15) At ^1300 °C the last BaSi 2 Os remaining could be also completely consumed by ALO3 contained in the remnant glassy phase of the CFA, according to reaction (8).…”
Section: Reaction Mechanism For the Formation Of Celsianmentioning
confidence: 99%
“…CFA is a byproduct of coal-burning power plants, whose main chemical constituents are Si0 2 and A1 2 0 3 , and whose main mineralogical components are quartz, mullite (A16SÍ2O13) and a highly reactive amorphous phase [15]. Millions of Tons of CFA are produced all over the world each year, most of which are discarded, with minimum use mainly as additive for Portland cement.…”
Section: Introductionmentioning
confidence: 99%
“…Mining is considered to be one of the most dangerous anthropogenic activities affecting soil quality. Another important factor is the presence of industrial sources of pollution, like smelters, coal burning plants or cement mills (Hulett et al 1980). Here, the distance from sources of pollution is essential (Albasel and Cottenie 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Ugurlu (2004) indicated that the main problem related to fly ash disposal was the residue heavy metal content. Numerous experimental studies show that toxic trace metals can be leached from fly ash (Georgakopoulos et al 2002;Baba and Kaya 2004;Baba and Ayyıldız 2006;Burcu et al 1997;Campbell et al 1978;Davison et al 1974;Gehrs et al 1979;Hulett et al 1980;Hansen and Fisher 1980;Klein et al 1975).…”
Section: Mining Activitymentioning
confidence: 99%